Взаємозв’язок агресивності й особистісних особливостей у здобувачів вищої освіти - Дейниченко, Л. М.; Deinychenko, L. M.; Маннапова, К. Р.; Mannapova, K. R.; ORCID: http://orcid.org/0000-0003-3754-4637; Раджабова, С. Ш.; Radzhabova, S. Sh. (Габітус. - 2023. - Вип. 46. - С. 80-84, 2023)
Висвітлено результати дослідження особливостей взаємозв’язку між агресивністю й особистісними особливостями здобувачів вищої освіти. Дослідження агресивності та ворожості здобувачів вищої освіти показало, що в них спостерігається підвищений рівень таких показників, як: фізична агресія, непряма агресія, негативізм, образа, підозрілість, вербальна агресія та відчуття провини. Встановлено взаємозв’язки між інтелектуальними, емоційними та комунікативними якостями та різними формами агресивності, ворожості. Усі особистісні риси, так чи інакше, впливають на конкретні форми агресивності та ворожості. Різниця – у ступені вираженості риси та її взаємозв’язку з певною формою агресивної поведінки.

The problem of aggressiveness is one of the traditional and topical problems of modern psychology. Theories of aggression that exist today explain the causes and mechanisms of aggressive human behavior in different ways. The frustration theory of aggression and the theory of social learning received the most experimental confirmation. In addition to being destructive, aggression also performs an adaptive function, it contributes to the maintenance of life and is a reaction to a threat to vital needs. Personal factors causing an increase in the level of aggressiveness are: increased hostility and irritability, anxiety and depressive states, emotional reactivity, negative affectivity, inadequate self-esteem, peculiarities of the motivational sphere, low level of intellectual development, antisocial personality orientation, envy, tendency to attribute aggressive intentions to others etc. Among the factors that prevent the manifestation of aggressiveness, the following are distinguished: the possibility of punishment, love, friendly relations, as well as such personal qualities as: moderation, tolerance, prudence, non-conflict, awareness, self-control. The study of aggressiveness and hostility of students of higher education showed that they have an increased level of such indicators as: physical aggression, indirect aggression, negativism, resentment, suspicion, verbal aggression, and a sense of guilt. The study of the personal characteristics of the students of education showed that the level of development of intellectual abilities is relatively low; indicators of emotional and volitional factors in the subjects are not pronounced and, accordingly, insufficiently developed; Among the indicators of the communicative block of factors, the following are pronounced: sociability, trustworthiness, difficulty in recognizing the hidden motives of other people, dependence on group opinion and behavior. With the help of correlation analysis, the relationship between intellectual, emotional and communicative qualities and various forms of aggressiveness and hostility was established. All personal traits, in one way or another, affect specific forms of aggressiveness and hostility. The difference is in the degree of expression of the trait and its relationship with a certain form of aggressive behavior.

Отражены результаты исследования особенностей взаимосвязи между агрессивностью и личностными особенностями соискателей высшего образования. Исследование агрессивности и враждебности соискателей высшего образования показало, что у них наблюдается повышенный уровень таких показателей, как физическая агрессия, косвенная агрессия, негативизм, оскорбление, подозрительность, вербальная агрессия и чувство вины. Установлены взаимосвязи между интеллектуальными, эмоциональными и коммуникативными качествами и разными формами агрессивности, враждебности. Все личностные черты так или иначе влияют на конкретные формы агрессивности и враждебности. Разница – в степени выраженности черты и ее взаимосвязи с определенной формой агрессивного поведения.
The relationship of aggressiveness and personal characteristics in higher education acquires
Дейниченко, Л. М. Взаємозв’язок агресивності й особистісних особливостей у здобувачів вищої освіти / Дейниченко Л. М., Маннапова К. Р., Раджабова С. Ш. // Габітус. - 2023. - Вип. 46. - С. 80-84. - DOI: https://doi.org/10.32782/2663-5208. 2023.46.11.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; здобувачі вищої освіти; students of higher education; соискатели высшего образования; агресивність; aggressiveness; агрессивность; ворожість; hostility; враждебность; особистість; personality; личность; особистісні особливості; personal characteristics; личностные особенности; юнацький вік; youthful age; юношеский возраст